LEXICO-SEMANTIC TRANSFORMATIONS IN THE UKRAINIAN TRANSLATION OF “MATILDA” BY ROALD DAHL - ОСТАПЕНКО, Світлана; КУЦ, Марія (Current Issues of Foreign Philology, 2022)
The purpose of the article is to analyze the application of lexical and semantic transformations in the process of translation of “Matilda” by Roald Dahl into Ukrainian, carried out by V. Morozov, and carry out their comparative analysis. The main scientific results are obtained applying a set of general scientific and special methods of research, namely: analysis and generalization of scientific and educational-methodical literature on the problems of translation transformations; theoretical generalization, analysis and synthesis; holistic and integral approaches to the study of linguistic phenomena; comparative, descriptive and analytical methods. In translation process of “Matilda” V. Morozov applied all types of lexico-semantic transformation: synonymous substitution, calque, descriptive translation, contextual substitution, transcoding, antonymous translation, compression, decompression, permutation, transposition, and concretization of meaning. Most often, the transformation of synonymous substitutions, transposition, permutation and calque were used, less often – antonymous translation, descriptive translation and generalization of meaning. Summing up the carried-out analysis, it’s possible to draw a conclusion that in most cases transformations are justified. Lexico-semantic transformations play an important role in the process of translation, providing the text with dynamics, enhancing expressivity, serving to enhance the image-expressive functions of a language. It is important in the process of translation to convey not only the content but also the mood with which the work was created. Therefore, most of the transformations were of complex nature: to achieve adequacy – the main goal of translation – the translator applied several transformations simultaneously.